Understanding Income Inequality in Ireland - Roantree, Barra (Statistical and Social Inquiry Society of Ireland, 2020)
This paper shows that inequality in disposable income has fallen substantially in Ireland between 1987 and 2017. However, inequality in market income has risen on most measures over the same period, leaving Ireland the most unequal country in the EU in terms of income before taxes, benefits and pensions. While benefit and pension payments do most to reduce the absolute level of inequality, it is Ireland’s highly progressive tax system that does most to reduce inequality relative to other EU countries, leaving us with a level of income inequality that is very close to the EU average.
read before the Society, 23rd January and 27th February 2020 - Barrington Lecture 2019/2020
Keywords: disposable income inequality; market income inequality; taxation; 314.15